2019
DOI: 10.1002/pmrj.12124
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use by U.S. Adults with Self‐Reported Doctor‐Diagnosed Arthritis: Results from the 2012 National Health Interview Survey

Abstract: Background The use of complementary and alternative medicine (CAM) therapies have been reported for the management of arthritis. However, little is known about CAM use among adults with self‐reported doctor‐diagnosed arthritis. Objectives To determine (1) the prevalence and type of CAM use, (2) the difference in characteristics between CAM users and non‐CAM users, and (3) the factors related to CAM use, among U.S. adults with self‐reported doctor‐diagnosed arthritis. Design Secondary analysis of the 2012 Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
14
0
1
Order By: Relevance
“…In a cross-sectional study of adult patients with arthritis using the 2007 National Health Interview Survey (NHIS) data to investigate CAM use, a significant association between CAM use and gender was observed with women reporting higher utilization rate of CAM than their men's counterparts [11]. This was confirmed recently in the Zhang et al's studies using the 2012 NHIS data, where higher use of CAM among women was also noted [9, 10]. The higher utilization rate of CAM among women is believed to be due to its perceived benefits in improving the physical and mental wellbeing [10].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In a cross-sectional study of adult patients with arthritis using the 2007 National Health Interview Survey (NHIS) data to investigate CAM use, a significant association between CAM use and gender was observed with women reporting higher utilization rate of CAM than their men's counterparts [11]. This was confirmed recently in the Zhang et al's studies using the 2012 NHIS data, where higher use of CAM among women was also noted [9, 10]. The higher utilization rate of CAM among women is believed to be due to its perceived benefits in improving the physical and mental wellbeing [10].…”
Section: Introductionmentioning
confidence: 70%
“…According to a study that was conducted using nationally representative data of the US population to explore the prevalence of CAM utilization among patients with chronic health conditions, arthritis patients were found to be the highest users of CAM in comparison to other chronic health conditions [8]. It is estimated that around 30–41% of adults with arthritis in the US are CAM users [912]. Various modalities of CAM are commonly used for the treatment of arthritis such as homeopathy, acupuncture, naturopathy, chiropractic or osteopathic manipulation, and massage [1217].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Canadian study found that 33.9% of patients with juvenile idiopathic arthritis used CAM therapies [13]. Several studies from the United States have estimated that 30-41% of adults with arthritis use CAM [14][15][16][17], while CAM use among youth with juvenile idiopathic arthritis has been found to be 72% [18]. Another study found that 40% of Australians who suffer from osteoarthritis use CAM [19].…”
Section: Introductionmentioning
confidence: 99%
“…Current best practice recommendations for hip and knee OA include a holistic approach to diagnosis and care that may incorporate education and self-management, pharmacological and non- older adults with knee OA found that about one-third used at least one or more complementary medicines or therapies (CMTs) to manage their OA, but that such use was to some degree inconsistent with treatment guidelines (Yang, Dubé, Eaton, McAlindon, & Lapane, 2013). A recent US population-based study similarly found that more than one-third of adults with arthritis sought complementary care to manage their health, concluding that dialogues that foster open and nonjudgmental communication and sharing between conventional and complementary healthcare providers and patients should be encouraged, to facilitate best possible patient care (Zhang et al, 2019).…”
mentioning
confidence: 99%